THE RELATIONSHIP BETWEEN PARENTING PATTERNS AND SPEECH DELAY IN CHILDREN AT THE GENERAL HOSPITAL ADAM MALIK HAJI CENTRE IN 2023 - Sinaga, Rosmani; Tantri, Salda May; Marliani; Simanjuntak, Emma Dosriamaya Noni Br. (Journal of Public Health Science, 2024)
Background: From the initial survey data obtained from the medical records of the Central General Hospital Haji Adam Malik Medan throughout 2022 there were 272 children who had been diagnosed with speech delay from the doctor and were undergoing outpatient care in the children's poly room. Methods: This type of research uses analytical research with a cross sectional design with a study population of 272 parents of children who are undergoing outpatient care in the children's poly room. The number of samples used was 73 samples obtained using the slovin formula. Data analysis techniques using univariate and bivariate analysis. Results: The results obtained from the results of the Bivariate test resulted in a p_value of 0.021 and was below 0.05, so it was stated that the results of the study showed a significant relationship between parenting patterns and speech delay problems in children. Conclusion: The results obtained from the results of the Bivariate test resulted in a p_value of 0.021 and was below 0.05, so it was stated that the results of the study showed a significant relationship between parenting patterns and speech delay problems in children. So that Ha accepts and H0 is rejected. It is recommended to respondents to be able to provide supportive parenting in order to reduce the risk of speech delay in children.